Genotypic distribution of Staphylococcus aureus colonizing children and adolescents in daycare centers, an outpatient clinic, and hospitals in a major Brazilian urban setting - Neto, Egidio Domingos André; Guerrero, Jaclyn; Snyder, Robert E.; Pereira, Renata Freire Alves; de Fátima Nogueira de Freitas, Maria; Silva-Santana, Giorgio; Riley, Lee W.; Aguiar-Alves, Fábio (Diagnostic microbiology and infectious disease, 2020)
Staphylococcus aureus nasal colonization is a major risk factor for infection. Studies have suggested an epidemiologic shift in the methicillin-resistant S. aureus (MRSA) strains that circulate in Brazil. We conducted cross-sectional studies of MRSA carriage among 1) children and adolescents in community daycare centers, 2) an outpatient clinic, and 3) hospitals in a large Brazilian metropolitan setting. There were 1.500 study subjects, 500 from each locale: 768 (51.2%) carried S. aureus whereas 150 (10%) of these were colonized with MRSA. The most common lineages were the Southwest Pacific (SWP) and the Pediatric clones in all three groups. Roughly 50% of SWP carried Panton-Valentine leukocidin (PVL) (p < 0.01) genes while 63.3% of the Pediatric clones were resistant or intermediately resistant to erythromycin (p < 0.01). This study describes a clonal change of the Brazilian epidemic clone (BEC) to the Pediatric and SWP lineages in Brazil. This finding has implications for clinical management of MRSA infections.